Caracterização e avaliação biológica do colágeno marinho de esponjas incorporado na hidroxiapatita para a engenharia do tecido ósseo - Parisi, Julia Risso (2019)
Fractures cause non-union and delay in bone consolidation, those problems are associated with a substantial physical incapacity and high socioeconomic costs and it’s considered an important clinical challenge. In this context, some biomaterials have been investigated to accelerate the consolidation of fractures and to be effective for bone grafting. One of the most promising strategies to improve the biological performance of bone grafts is the combination of different biomaterials. In this context, the aim of this work was to evaluate through in vitro assay (study I) and in vivo study (study II) the effects of the incorporation of marine spongin (SPG) from Aplysina fulva into Hydroxyapatite (HA) for bone tissue engineering proposals. In the study I, SPG and HA scaffolds with different proportions (HA/SPG 90/10 and HA/SPG 70/30) were produced. For this, the following procedures were evaluated: scaffolds mass loss after incubation, pH, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and in vitro cell viability. Regarding study II, HA and HA/SPG 70/30 scaffolds were produced and SEM analysis was performed to characterize the samples. Also, in order to evaluate the in vivo tissue response, samples were implanted into a tibial bone defect in rats. Histopathological, immunohistochemistry and biomechanical analyzes were performed after 2 and 6 weeks of implantation to investigate the effects of the material on bone repair. The results of study I showed that pH measurements presented no statistical difference between the groups. Moreover, a higher mass loss was observed for HA/SPG70/30 compared to the other groups for all experimental periods. Moreover, SEM representative micrographs showed the degradation of the samples. FTIR analysis demonstrated the absorption peaks of the materials. A higher L929 cell viability for HA/SPG 70/30 was observed compared to HA and HA/SPG 90/10 on days 7 of culture. Furthermore, HA/SPG 70/30 showed a significant lower MC3T3 cell viability compared to HA and HA/SPG 90/10 on day 1. After 3 days the HA group showed lower cell viability when compared to the control group and HA/SPG 70/30. In the study II, it was possible to observe through the SEM results that SPG were successfully inserted in the HA, forming a homogeneous scaffold. The histological analysis demonstrated that the HA/SPG (70/30) group presented an accelerated material degradation and enhanced newly bone formation compared to the HA group. Additionally, histomorphometry analysis showed higher values of %BV/TV and N.Ob/T.Ar for HA/SPG (70/30) compared to the HA. Immunohistochemical analyzes, the Runx-2 immunolabelling was observed in granulation tissue and newly formed bone for all experimental groups. Furthermore, HA/SPG (70/30) showed an increase of immunolabelling compared to the other groups. Moreover, the VEGF immunolabelling was observed in granulation tissue for all experimental groups however, no difference was found. The biomechanical analysis demonstrated similar values for all groups. Considering the results of the two studies it is concluded that SPG can be used as an additive in HA, especially the one mimicking the composition of bone (with 70% of HA and 30% of SPG), providing an improvement in biological performance for bone regeneration applications. However, further long-term studies should be carried out to provide additional information regarding the material degradation and bone regeneration.